2015
DOI: 10.1002/wcm.2659
|View full text |Cite
|
Sign up to set email alerts
|

Fair coding for inter‐session network coding in wireless mesh networks

Abstract: Because of the broadcast and overhearing capability of wireless networks, network coding can greatly improve throughput in wireless networks. However, our investigation of existing inter‐session network coding protocols found that the short‐term unfairness that existed in 802.11‐based medium access control (MAC) protocols actually decreases the coding opportunity, which in turn compromises the throughput gain of network coding. To alleviate the negative impact of this unfairness, we propose a coding‐aware cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…Moreover, in [23] a study of the effects of network coding on the aggregated throughput in WMNs is provided; it is observed that the throughput can be considerably increased with the use of NC techniques. Besides, in [24] the authors propose FairCoding, which is a cross-layer protocol optimizing the coordination among the network coding and the MAC layer protocols; they observe that FairCoding increases the number of coding opportunities as well as the average transmission rate of WMNs, reaching an improvement of 20%. Finally, in [25] the authors jointly optimize NC and opportunistic routing in WMNs; they also provide a taxonomy of protocols considering both mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in [23] a study of the effects of network coding on the aggregated throughput in WMNs is provided; it is observed that the throughput can be considerably increased with the use of NC techniques. Besides, in [24] the authors propose FairCoding, which is a cross-layer protocol optimizing the coordination among the network coding and the MAC layer protocols; they observe that FairCoding increases the number of coding opportunities as well as the average transmission rate of WMNs, reaching an improvement of 20%. Finally, in [25] the authors jointly optimize NC and opportunistic routing in WMNs; they also provide a taxonomy of protocols considering both mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…El mecanismo de control de acceso el medio (MAC) es muy importante para la implementación de la codificación de red. En [92], Yang et al demuestran que la inequidad de este mecanismo es un factor que reduce las oportunidades de codificación, limitando significativamente los beneficios de la codificación de red. Los autores proponen un mecanismo denominado como FairCodig para atender este problema.…”
Section: Fair Codingunclassified